2006
DOI: 10.1213/01.ane.0000230601.64098.cc
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of the Nociceptin Receptor in the Antinociceptive Action of Nitrous Oxide

Abstract: Nociceptin and its receptor are widely expressed in the central nervous system and are involved in the modulation of nociception. We have previously reported that the minimum anesthetic alveolar concentrations for volatile anesthetics do not differ between nociceptin receptor knockout (NOP-/-) mice and wild-type (NOP+/+) mice. In the present study, we investigated whether the nociceptin system is involved in the antinociceptive action of nitrous oxide. Using the acetic acid-induced writhing test, we showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…10 High concentrations of isoflurane (1.5 MAC) depressed c-Fos expression in spinal lamina II, whereas fentanyl reduced expression in lamina V. 11 Results with nitrous oxide have been controversial. While some have reported little or no effect of nitrous oxide 44,45 or even an increase, 46 many studies, including the present one, demonstrate that nitrous oxide alone reduced dorsal horn c-Fos expression. 11,47,48 Thus, in the present work, nitrous oxide prevented c-Fos expression in superficial dorsal horn (lamina I-II).…”
Section: Discussioncontrasting
confidence: 53%
“…10 High concentrations of isoflurane (1.5 MAC) depressed c-Fos expression in spinal lamina II, whereas fentanyl reduced expression in lamina V. 11 Results with nitrous oxide have been controversial. While some have reported little or no effect of nitrous oxide 44,45 or even an increase, 46 many studies, including the present one, demonstrate that nitrous oxide alone reduced dorsal horn c-Fos expression. 11,47,48 Thus, in the present work, nitrous oxide prevented c-Fos expression in superficial dorsal horn (lamina I-II).…”
Section: Discussioncontrasting
confidence: 53%
“…Nociceptin has a potent antinociceptive effect in the abdomen, as shown in the acetic acid-induced abdominal pain model in mice (Himukashi et al, 2006). This suggests that the activation of NOP receptors is crucial for abdominal nociceptive signaling and that the NOP ligands may alleviate GI tract-related pain (Himukashi et al, 2006). Recently, Agostini et al (2009) confirmed the antinociceptive action of nociceptin, characterized by the changes in the visceromotor response to colorectal distension in the rat model of TNBS-induced colitis.…”
Section: Discussionmentioning
confidence: 95%
“…There are two types of abdominal pain: somatic, which is musculoskeletal; and visceral, caused by stretching of the viscera by obstruction or widely affected inflammation. Nociceptin has a potent antinociceptive effect in the abdomen, as shown in the acetic acid-induced abdominal pain model in mice (Himukashi et al, 2006). This suggests that the activation of NOP receptors is crucial for abdominal nociceptive signaling and that the NOP ligands may alleviate GI tract-related pain (Himukashi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…N/OFQ and NOP are widely expressed in the central nervous system [7,8] and have been shown to be involved in the modulation of nociceptive signals. Although we previously reported that the analgesic effect of N 2 O was markedly smaller in NOP-defi cient mice than in wild-type mice [9], it is not known whether NOP antagonists affect N 2 Oinduced analgesia. The aim of the present work was to investigate the effect of a NOP antagonist, JTC-801, on of baseline TFL, each mouse was exposed to the mixed gas for 30 min, and then transferred outside the chamber to determine the post-treatment TFL.…”
Section: Abstract Nitrous Oxide · Analgesia · Nociceptinmentioning
confidence: 92%